Biorestraining potentials of marine macroalgae collected from Rameshwaram, Tamil nadu - Sorna kumari H; S, Anandhan (Journal of Research in Biology, 2011)
The marine ecosystem is the treasure place for many natural resources. In this study, about five different marine macroalgae were chosen to study the antibacterial activity and larvicidal activity of Aedes sp. About five different stranded strains of bacteria have been selected to detect the antibacterial activity of collected algae. Among the five algae collected, Gracilaria crassa and Hypnea valentia have shown maximum antibacterial activity in methanolic extraction by antibiosis of Kirby-Bauers method. The active biocompound from methanol was determined by using different solvent systems in TLC. The partially purified antibacterial compound was identified as saponins by phytochemical tests. Larvicidal bioassay was carried out with the two algae Gracilaria crassa and Hypnea valentia. The LC50 determined by the Gracilaria crassa and Hypnea valentia was noted as 52.2 and 53.4 respectively